Snow, Smoke, and Swamp: Environmental Considerations of Seventeenth-Century Colonial Warfare in Southern New England - Wilson, Jamie G. (Kansas State University. Dept. of History, 2018)
Research finds that environmental factors such as the ecology of the swamp, the terrain, and winter weather had a substantial impact on The Great Swamp Fight of December 19, 1675 during King Philips. Comparison prior battles such as the Mystic River Massacre forty years prior have been overly simplistic. While the tactics used by the English against the Narragansett in the Great Swamp seem inspired by Mystic, the physical landscape and weather conditions altered the outcome. Through environmental histories of the region, first person accounts, and concomitant histories of King Philip’s War and the Pequot War, the role of the environment in shaping The Great Swamp fight is clear.
Keywords: Environmental History; Colonial Fortifications; Native Ameican Warfare; Wampum; Winter Warfare; Rhode Island